Chinese Craft in E-Commerce - Katarzyna MAZUR-KAJTA; Elzbieta KARAS (Communications of International Proceedings, 2020)
The purpose of this article is to answer the following questions: Does Chinese craftsmanship also have a future in the e-commerce space? How do Chinese craftsmen find their professional activity in the field of e-commerce? What issues related to Chinese crafts and e-commerce are the topics most often shown by scientific articles and the media? The research used an analysis of the literature on the subject, reports, and the works of Polish, English and Chinese journalists published on the Internet. The article describes the formation of the Chinese internet industry, which has surprised many with its dynamics and scale over the past 30 years. Chinese craftsmanship in the area of e-commerce was presented from the perspective of shaping the spirit of craftsmanship as well as changes and modern trends in the contemporary economy. This paper analyzes the profiles of the "young" generation of craftsmen, who show an openness to changes and introducing new solutions, as well as the willingness to follow the latest trends. The presented results are important for the scientific community, mainly due to the apparent lack of materials related to craftsmanship and e-commerce; as well as for groups of craftsmen planning to expand their business with activity in the e-commerce space. Research results can contribute to increasing the knowledge about the activity of craftsmen in the field of e-commerce, and exploring the information presented by the Polish, English and Chinese media.
Keywords: E-commerce; People's Republic of China; crafts; economic culture.